Investment Financing and Financial Development: Evidence from Viet Nam - O’Toole, Conor; Newman, Carol (Review of Finance, 2017)
Abstract This article explores whether financial development reduces external financing constraints faced by firms, a key channel through which finance impacts economic growth. Using an extensive firm-level dataset from Viet Nam, we use a structural Q model of investment estimated using a generalized method of moments technique. We focus on three aspects of financial development: financial depth, state-owned enterprise (SOE) use of finance and, the degree of market-driven, commercial bank financing in the economy. Our data allow us to measure financial development at the province level, providing rich within-country variation. We find that financial development reduces external financing constraints for firms thus facilitating higher investment activity. Financing constraints are decreasing in credit to the private sector, increasing in the use of finance by SOEs and decreasing in the degree to which finance is allocated on market-terms by commercial banks.